Development finance and the development of financial equity markets: the case of the oil and gas industry in Africa - Africa, Andrea (My University, 2013)
This paper analyses the provision of development finance to oil and gas exploration and production (E&P) firms through Development Finance Institutes (DFIs) in Africa. The paper aims to determine the state of equity markets and development finance in Africa and the level at which they contribute to the financing of oil and gas projects in Africa. The main question to be answered: is small firm participation sustainable in the oil and gas industry if equity markets do not develop to meet the financing needs in Africa? It is found that development finance contributes a small proportion of capital into oil and gas deals and financial equity markets play an even smaller role in garnering finance for capital intensive projects in the oil and gas industry as most finance is sourced externally or from internal cash flows. Small firms tend to reduce their interest in oil and gas projects based on lack of access to domestic finance through equity markets and limited development finance availability.
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2013.
Keywords: Development finance; Financial equity markets; Africa; Oil industry; Gas industry